2008
DOI: 10.1158/1078-0432.ccr-07-0586
|View full text |Cite
|
Sign up to set email alerts
|

Serum Proteomics and Biomarkers in Hepatocellular Carcinoma and Chronic Liver Disease

Abstract: Purpose: Proteomic profiling using surface enhanced laser desorption/ionization time of flight mass spectrometry (SELDI-TOF MS) enables the identification of biomarkers for cancer.We evaluated the sensitivity and specificity of SELDI-TOF MS for detection of established hepatocellular cancer (HCC) and compared it against a-fetoprotein (AFP), Lens culinaris agglutinin^reactive AFP (AFP-L3), and prothrombin induced by vitamin K absence-II (PIVKA-II). Experimental Design: Forty-one patients with HCC and 51 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
123
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(127 citation statements)
references
References 36 publications
3
123
1
Order By: Relevance
“…Serum XAGE-1b expression in human HCC patients. Serum tumor markers have been widely studied in HCC diagnosis and prognosis (17)(18)(19)(20). Thus, the serum XAGE-1b levels and the associations of its expression with HCC diagnosis and prognosis were further analyzed.…”
Section: Association Of Xage-1b Expression With Prognosismentioning
confidence: 99%
“…Serum XAGE-1b expression in human HCC patients. Serum tumor markers have been widely studied in HCC diagnosis and prognosis (17)(18)(19)(20). Thus, the serum XAGE-1b levels and the associations of its expression with HCC diagnosis and prognosis were further analyzed.…”
Section: Association Of Xage-1b Expression With Prognosismentioning
confidence: 99%
“…Alpha-Fetoprotein (AFP) has mainly been used for diagnosis of HCC; however, its sensitivity and specificity are not satisfying that the Practice Guidelines of the American Association for the Study of Liver Diseases (AASLD) has rejected its use, since 2010, whether for the surveillance or the diagnosis of HCC [4].…”
Section: Introductionmentioning
confidence: 99%
“…Proteomics is a similarly evolving field aiming to identify the complete proteome, including post-translational modifications. Small initial studies have revealed some positive findings, for example, an eleven peptide signature reported to have a better sensitivity and specificity for HCC than traditional serum markers (AFP and prothrombin induced by vitamin K absence-II [PIVKA-II]) (32). It remains to be seen whether these small studies can be reproduced on a larger scale and developed into a practical, clinical assay.…”
Section: Diagnostic Developmentsmentioning
confidence: 99%